2016
DOI: 10.1152/ajpgi.00010.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laryngeal restriction on pharyngeal peristalsis and biomechanics: Clinical implications

Abstract: To date, rehabilitative exercises aimed at strengthening the pharyngeal muscles have not been developed due to the inability to successfully overload and fatigue these muscles during their contraction, a necessary requirement for strength training. The purpose of this study was to test the hypothesis that applying resistance against anterosuperior movement of the hyolaryngeal complex will overload the pharyngeal muscles and by repetitive swallowing will result in their fatigue manifested by a reduction in phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 33 publications
1
33
0
6
Order By: Relevance
“…Contrary to the esophagus, a number of muscle groups are involved in pharyngeal motor function 13,16 and the pharyngeal deglutitive peristaltic pressure wave is generated by different muscle groups. For example, the generation of the most proximal part of the pharyngeal peristaltic pressure zone is mostly attributable to the contraction of the proximal pharyngeal constrictor and the velum, the middle part of pharyngeal contraction is attributable to the contraction of middle constrictor and tongue base while the pressures generated in the most distal part are attributed to the contraction of the distal pharyngeal constrictor and retraction/thrust of the tongue base.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the esophagus, a number of muscle groups are involved in pharyngeal motor function 13,16 and the pharyngeal deglutitive peristaltic pressure wave is generated by different muscle groups. For example, the generation of the most proximal part of the pharyngeal peristaltic pressure zone is mostly attributable to the contraction of the proximal pharyngeal constrictor and the velum, the middle part of pharyngeal contraction is attributable to the contraction of middle constrictor and tongue base while the pressures generated in the most distal part are attributed to the contraction of the distal pharyngeal constrictor and retraction/thrust of the tongue base.…”
Section: Discussionmentioning
confidence: 99%
“…All these are complimented by the contraction of pharyngeal longitudinal muscles contributing to pharyngeal shortening along with contraction of extrapharyngeal suprahyoid muscles. 13,16 Each of these muscle groups may be uniquely amenable to and demonstrate a unique response to a given intervention as has been shown in the case of velopharyngeal muscle group exhibiting increased pressure with swallowing of larger water volumes, 8 a response not reported for the rest of the pharynx.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the duration from the maximum position of the larynx to the opening of laryngeal vestibule closure was not significantly different but tended to be shorter than that of the normal group. When the larynx has reached the anterior and superior maximum position, the bolus passage resistance to the UES decreases . It is important how much bolus can be transferred during the duration from the maximum position of the larynx to the opening of laryngeal vestibule closure.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, we showed that applying resistance against anterosuperior movement of the hyolaryngeal complex during repetitive swallowing results in overload and fatigue of the pharyngeal and suprahyoid muscles evidenced by significant reduction in both pharyngeal deglutitive contractile pressure and maximum deglutitive hyolaryngeal excursion. This study, however, was not designed to evaluate strengthening of the target muscles. The aim of the present study therefore was to determine the effect of our proposed strength training exercise regimen based on the technique of Swallowing Against Laryngeal Restriction (SALR) on pharyngeal phase of swallowing biomechanics, pharyngeal motor function and upper esophageal sphincter (UES) opening in the elderly.…”
Section: Introductionmentioning
confidence: 96%
“…The success of strength training exercises depends on adequate overload and fatigue of the target muscles during contraction . In an earlier study, we showed that applying resistance against anterosuperior movement of the hyolaryngeal complex during repetitive swallowing results in overload and fatigue of the pharyngeal and suprahyoid muscles evidenced by significant reduction in both pharyngeal deglutitive contractile pressure and maximum deglutitive hyolaryngeal excursion. This study, however, was not designed to evaluate strengthening of the target muscles.…”
Section: Introductionmentioning
confidence: 97%